The impact of a pandemic on dental professionals' work and personal lives: A qualitative study with implications for primary healthcare workers - Al-Amer, Rasmieh; Ramjan, Lucie M.; Maneze, Della; Al-Rashdan, Omar; Villarosa, Amy R.; Salamonson, Yenna; George, Ajesh (Frontiers in Public Health, 2022)
During a pandemic, dentists face enormous challenges due to restrictions placed on their practice and the need to comply with biosafety measures. This study aimed to explore the impact of the COVID-19 pandemic and infection control measures on dentists and their practice in Jordan and the global implications for other primary healthcare workers. A qualitative exploratory study employing face-to-face or telephone interviews, was conducted with ten dentists from the 9th May to 20th September 2020. An inductive thematic approach to analysis was used identifying three themes, each with two accompanying subthemes: (1) Response to COVID-19 pandemic: (1a) Government response and (1b) People's response; (2) The effects of the pandemic and response measures: (2a) Impact on work and practice and (2b) Impact on personal and social life; (3) The unanticipated gains: (3a) Altruism and (3b) Leadership and change. Stringent infection control measures were implemented to slow the spread of the virus, however limited government support made implementation unsustainable and caused financial hardship. Lack of clear guidelines, changes in practice, social distancing measures, and altered social interactions, adversely impacted daily life, triggering mental distress. Misinformation influenced response to COVID safety measures. Despite the negatives, working during the pandemic reaffirmed dental professionals' roles and purpose, with strong leadership boosting morale. Education, adequate biosafety resources and clear guidelines or policies to support and sustain stringent infection control procedures are crucial in ensuring that measures are implemented to meet the safety requirements of the pandemic response. Promoting the well–being of the healthcare workforce is equally important. Finally, altruism and strong leadership among healthcare workers can contribute to a meaningful and humane pandemic response.